High CO2 Reduces Spoilage Caused by Botrytis cinerea in Strawberry Without Impairing Fruit Quality - Li, Hua; Yin, Yuwei; Affandi, Fahrizal Yusuf; Zhong, Caihong; Schouten, Rob E.; Woltering, Ernst J. (Frontiers in Plant Science, 2022)
High CO2 (> 20 kPa) conditions are beneficial for suppressing spoilage caused by Botrytis cinerea in strawberry fruit, however, these conditions are often accompanied by discoloration, off-flavors and faster softening. Stepwise increments of CO2 concentrations have been proposed to alleviate injuries in fruits caused by high CO2. Here, we investigated whether stepwise increments of CO2, up to 30 kPa and under a reduced O2 concentration is beneficial for reducing fungal spoilage without inducing CO2 injury symptoms in strawberry fruit. Based on recommended settings (5 to 10 kPa O2 with 15 to 20 kPa CO2), we first selected optimal O2 and CO2 concentrations that best reduced spoilage caused by B. cinerea in red ripe ‘Sonsation’ strawberry fruit. We found that higher O2 (10 kPa) and CO2 (20 kPa) concentrations were most beneficial to prolong strawberry fruit shelf life. Subsequently we studied the performance of red ripe ‘Arabella’ strawberry fruit stored at 5 °C under different controlled atmosphere (CA) conditions (10 kPa O2 with either 0, 20, or 30 kPa CO2). The CO2 concentrations were achieved either within eight hours, or in stepwise manners within the first four days of storage. 21 kPa O2 and 0 kPa CO2 served as control. Following storage for up to eleven days, spoilage incidence was assessed at 12 °C for five days. The application of high CO2 (20 and 30 kPa) combined with 10 kPa O2 greatly suppressed fruit spoilage during storage and subsequent shelf life. High CO2 suppressed respiration as well as maintained a higher pH and firmness in treated fruit. The level of total sugars did not change, but during storage, a substantial part of sucrose was converted into glucose and fructose, especially under high CO2 conditions. High CO2 did not affect ascorbic acid and anthocyanin levels. The stepwise increments of CO2 did not result in beneficial effects compared to the static application of high CO2. Our results show that ‘Arabella’ strawberry fruit are highly tolerant to elevated CO2 and can be stored under 30 kPa CO2 to prolong the shelf life.